Job Security Provisions and Employment - Lazear, Edward P. (Quarterly Journal of Economics, 1990)
European countries have enacted various job security provisions over the last 30 years. Employers are required to pay workers on separation or to give advance notice of termination. In anything less than a perfectly functioning market, there are effects of the provisions on employment. Incumbents are more likely to retain their jobs, but new workers are less likely to be hired. An examination of the European data suggests that severance pay requirements reduce employment.